Levocarnitine in the management of fatigue in levothyroxine treated hypothyroid patients - Akhter, Farjana; Dewan, Zesmin Fauzia; Hasnat, MA; Akhter, Selina (IMC Journal of Medical Science, 2020)
Background and objectives: Hypothyroid patients often complain of fatigue even after effective treatment. Thyroid hormone plays an important role in carnitine-dependent long chain fatty acid transport for oxidation and ultimate formation of ATP. Deficiency of L-carnitine has been presumed to disrupt ATP formation leading to fatigue. Present study was designed to assess the role of L-carnitine as a supplement to manage the fatigue state of hypothyroid patients. Methods: Hypothyroid patients receiving levothyroxine (L-T4) and suffering from fatigue symptoms were enrolled. Patients were randomly divided into Group A (Control group, n=35) and Group B (Experimental group, n=36). Patients of Group A were treated with L-T4 only and Group B patients received L-carnitine 2 g/day in addition to L-T4 therapy for 8 weeks. Fatigue was assessed by fatigue severity scale (FSS), physical fatigue (PF) and mental fatigue (MF) scores. Data regarding fatigue status, serum thyroid stimulating hormone (TSH) and free thyroxine (FT4) were collected at the beginning and after 8 weeks of intervention. Result: The mean age of Group A and Group B patients was 33.5±8.1 and 35.4±7.5 years respectively (p>0.05); and the mean body weight was 61.5±9.6 kg and 62.5±8.2 kg respectively (p>0.05). The mean baseline values of different fatigue scores and the serum TSH and FT4 levels of patients of two groups were identical and not significantly different (p>0.05). In Group-A patients, the mean MF score improved significantly (5.2±1.5 vs 4.6±1.4; p=0.01) from baseline score after 8 weeks while the FSS and PF scores did not improve significantly (p>0.05). In Group-B patients, the mean FSS, PF and MF scores improved significantly (p<0.01) from baseline score after 8 weeks of treatment with L-carnitine along with L-LT4 treatment. FSS, PF and MF scores of Group-B patients reduced significantly (p<0.01) compared to Group-A patients after 8 weeks of treatment. FSS, PF and MF scores improved in 88.9%, 77.8% and 47.2% cases respectively in Group-B compared to 20%, 14.3% and 5.7% cases in Group-A. L-carnitine was well tolerated and no severe adverse event was recorded. Conclusion: The results suggest that, administration of L-carnitine along with L-T4 in hypothyroid patients significantly reduced physical and mental fatigue. Ibrahim Med. Coll. J. 2019; 13(2): 45-52